If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -1) + -2(x + -3) = 2x + -3 Reorder the terms: 3(-1 + x) + -2(x + -3) = 2x + -3 (-1 * 3 + x * 3) + -2(x + -3) = 2x + -3 (-3 + 3x) + -2(x + -3) = 2x + -3 Reorder the terms: -3 + 3x + -2(-3 + x) = 2x + -3 -3 + 3x + (-3 * -2 + x * -2) = 2x + -3 -3 + 3x + (6 + -2x) = 2x + -3 Reorder the terms: -3 + 6 + 3x + -2x = 2x + -3 Combine like terms: -3 + 6 = 3 3 + 3x + -2x = 2x + -3 Combine like terms: 3x + -2x = 1x 3 + 1x = 2x + -3 Reorder the terms: 3 + 1x = -3 + 2x Solving 3 + 1x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 1x + -2x = -3 + 2x + -2x Combine like terms: 1x + -2x = -1x 3 + -1x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + -1x = -3 + 0 3 + -1x = -3 Add '-3' to each side of the equation. 3 + -3 + -1x = -3 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = -3 + -3 -1x = -3 + -3 Combine like terms: -3 + -3 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 4x-2(x-4)=-7+4x+2 | | 23+3h=54 | | 268=215-y | | 1/5(-10a)= | | 9a-17b+15a= | | -0.7(3a)= | | 9x-(x-1)=17 | | 4p(np-z)=0 | | 0.89x+4=1.09x | | 7x+14=2x-36 | | -4x-2.5x+11+3.6x-16.4= | | 3x-11y-6x= | | 3(x-2)=-26-7x | | 7z-1=2(4z-3) | | (x+64)=(2x+39) | | 40+5x=5(7+2x) | | 3/4x-9=7 | | (3/2)x-163x | | -23=-9f-4f | | 2x+4y+2-y-9x-5= | | 4.75t+5=13.5t+12 | | Y=cos(5*x)+sin(5*x) | | 3m-4n-7=8m+n-6 | | 24-8x=-2(4x+10) | | 3y+-5=5y | | 90+(3x-1)+31=180 | | 4.19/4 | | 7(5x-3)=10 | | 2x(100/45):3x(100/36) | | 9h-3-6h=16 | | 2(3x+6)+3(3x-4)= | | 0.06/1=x/30 |